DEVELOPMENT OF MARKETING STRATEGY AND PLAN IN ISLAM (Case Study of Muslim Clothing Store in Sambas Malay Market) - Arpiati Arpiati (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
Sudi Muslim Clothing Store in addition to applying the theory and concepts of conventional marketing strategies, it also applies an Islamic marketing strategy which consists of the first three main points, the application of Islamic marketing characteristics; second, the application of Islamic business ethics; third, following the marketing practices of the Prophet Muhammad SAW. The Sudi Muslim Clothing Store imitates the marketing practices of the Prophet Muhammad SAW starting from segmentation and targeting, positioning. for capital problems in business development, poor road access is narrow and damaged roads and then there is no security member for shops/parking and sales promotions that cannot be maximized, and also the lifestyle or purchasing power of consumers around the store is not fixed or changing Besides that, human resources are also lacking in quality, especially in marketing and unable to maximize prices for products sold at the Sudi Muslim Clothing Store, Pasar Melayu Sambas.